2020
DOI: 10.11622/smedj.2019102
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure goal attainment in multi-ethnic Asian patients with hypertension and dyslipidaemia in primary care

Abstract: Introduction: Hypertension and dyslipidaemia are major risk factors for cardiovascular diseases, and achieving treatment goals mitigates such risks. This study determined demographic and medication-related factors associated with blood pressure (BP) goal attainment in patients with concomitant hypertension and dyslipidaemia. Methods: This paper consisted of a sub-analysis of the Lipid HEALTH study, a questionnaire survey focusing on adult Asian patients with both dyslipidaemia and hypertension. Intervieweradmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In this study, out of 650 subjects, 39.54% achieved the target BP. This is in agreement with studies conducted in Singapore which recorded 49.7%[ 9 ] and in Ethiopia 25.6%. [ 10 ] On the other hand, studies conducted in Australia[ 11 ] reported higher BP control.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, out of 650 subjects, 39.54% achieved the target BP. This is in agreement with studies conducted in Singapore which recorded 49.7%[ 9 ] and in Ethiopia 25.6%. [ 10 ] On the other hand, studies conducted in Australia[ 11 ] reported higher BP control.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies suggested that abnormal serum lipid levels may contribute to hypertension and that correcting serum lipid abnormalities may help control blood pressure. 18 19 Dyslipidaemia is often still neglected in patients with hypertension, especially in those at higher risk of cardiovascular and cerebrovascular diseases. 20 Therefore, it is of great importance to study the serum lipid profiles of patients with hypertension in the prevention and treatment of cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypertension often have dyslipidaemia. Some studies suggested that abnormal serum lipid levels may contribute to hypertension and that correcting serum lipid abnormalities may help control blood pressure 18 19. Dyslipidaemia is often still neglected in patients with hypertension, especially in those at higher risk of cardiovascular and cerebrovascular diseases 20.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, 49.7% of patients treated for hypertension in primary care were reported with good blood pressure (BP) control. 7 While in Malaysia, the proportion of patients with good hypertension control is lower at 37.4%. 8 The differences in the proportion of good BP control warrants a comparison of their health behaviour profiles in the two countries as they have similar multi-ethnic background and culture.…”
Section: Introductionmentioning
confidence: 99%